1992
DOI: 10.3164/jcbn.12.201
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Insulin Secretion and Increase of Plasma Non-Esterified Fatty Acids Induced by Biotin Deficiency in Osteogenic Disorder Shionogi Rats.

Abstract: SummaryWe determined the changes in the sources of energy supply

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Therefore we presume that the biotin depletion observed in diabetic patient may interfere with pyruvate catabolism as a consequence of reduced activity of the enzyme, resulting in an accumulation of pyruvate and subsequent hyperglycemia. Experimentally it has been shown that there is an impairment in glucose catabolism in biotin-deficient rats [4,[12][13][14][15] and that administration of a biotin supplement counteracts the defect in the oral glucose tolerance and in the insulin response to the oral glucose load in diabetic kk mice [1]. In the present patients, biotin administration decreased the serum levels of pyruvate and lactate.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Therefore we presume that the biotin depletion observed in diabetic patient may interfere with pyruvate catabolism as a consequence of reduced activity of the enzyme, resulting in an accumulation of pyruvate and subsequent hyperglycemia. Experimentally it has been shown that there is an impairment in glucose catabolism in biotin-deficient rats [4,[12][13][14][15] and that administration of a biotin supplement counteracts the defect in the oral glucose tolerance and in the insulin response to the oral glucose load in diabetic kk mice [1]. In the present patients, biotin administration decreased the serum levels of pyruvate and lactate.…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, it seems unlikely that biotin directly stimulates the insulin release with a resultant decrease in the blood glucose level. On the other hand, we demonstrated that the plasma insulin level remarkably declined so that insulin synthesis or the excretion system of the rats may be impaired at an early stage during the course of development of biotin deficiency in osteogenic disorder Shionogi rats [4]. Furthermore, the plasma insulin secreted in response to the glucose load in the deficient rats was approximately one-third the concentration of that in the control rats.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…There are acetyl-CoA carboxylase involved in fatty acid synthesis, pyruvate carboxylase involved in glucose metabolism, and propionyl-CoA carboxylase and f3-methylcrotonyl-CoA carboxylase involved in the catabolism of amino acids. Biotin depletion, therefore, causes metabolic abnormalities such as an impairment of glucose utilization [14][15][16], a reduced synthesis of prostaglandins (PGs) [17] and of their precursor fatty acids [18][19][20][21], and an accumulation of abnormal catabolites derived from amino acids [22,23]. However, no information is available concerning the effect of biotin depletion on these metabolic abnormalities in patients with SCCH, nor is it known whether the metabolic abnormalities are associated with the pathogenesis of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…All animals were fed a biotin-deficient diet (20% freeze-dried raw egg white as a protein source). The composition of the experimental diet was reported previously [15,16]. The rats were given free access to the semisynthetic diet and drinking water; and the control and the biotin-deficient groups were given an intraperitoneal injection of 0.5 ml of saline containing 1001ag of biotin and saline only, respectively, once a week.…”
Section: Methodsmentioning
confidence: 99%